Analysis of fluorescently labeled glycosphingolipid-derived oligosaccharides following ceramide glycanase digestion and anthranilic acid labeling. - Neville, D; Coquard, V; Priestman, D; te Vruchte, D; Sillence, D; Dwek, R; Platt, F; Butters, T (2004)
Interest in cellular glycosphingolipid (GSL) function has necessitated the development of a rapid and sensitive method to both analyze and characterize the full complement of structures present in various cells and tissues. An optimized method to characterize oligosaccharides released from glycosphingolipids following ceramide glycanase digestion has been developed. The procedure uses the fluorescent compound anthranilic acid (2-aminobenzoic acid; 2-AA) to label oligosaccharides prior to analysis using normal-phase high-performance liquid chromatography. The labeling procedure is rapid, selective, and easy to perform and is based on the published method of Anumula and Dhume [Glycobiology 8 (1998) 685], originally used to analyze N-linked oligosaccharides. It is less time consuming than a previously published 2-aminobenzamide labeling method [Anal. Biochem. 298 (2001) 207] for analyzing GSL-derived oligosaccharides, as the fluorescent labeling is performed on the enzyme reaction mixture. The purification of 2-AA-labeled products has been improved to ensure recovery of oligosaccharides containing one to four monosaccharide units, which was not previously possible using the Anumula and Dhume post-derivatization purification procedure. This new approach may also be used to analyze both N- and O-linked oligosaccharides.